(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
This text aims at summarizing the articles published in this issue of BioLaw Journal – Rivista di BioDiritto devoted to the vital and crucial encounter of religion and biolaw. The five key areas of “categories”, “sources”, “space”, “time” and “principles” are identified. The resulting challenge seems to concern at the same time the shaping of knowledge on the interaction of religion and biolaw and the power to determine its future direction.